BANKING SECTOR REFORMS AND THE EMERGING INEQUALITIES IN COMMERCIAL CREDIT DEPLOYMENT IN INDIA - Narayana (CSDWP300, 2000)
Banking sector reforms, which is a major component of Macroeconomic Adjustment Programme in India, has changed the trends and patterns of banking over the last six to seven years. This paper seeks to analyse the trends in credit deployment by industry, by bank group, by rural and urban areas, and by states over the recent period. The argument of the paper is that serious regional and sectoral inequalities are developing in the deployment of commercial credit in this country. The economic reasoning for nationalising the major banks in 1969 was the imperfection in the allocation of credit. With bank nationalisation there was a rapid expansion of the banking network into rural and semiurban areas, and an increase in the share of agriculture and small industry and transport and trade in the total credit deployed. The banking sector reforms have changed this trend. The number of loan accounts has fallen by 60 lakhs in six years, and the fall is largely confined to agriculture, transport operators and trade. The new private banks and foreign banks are increasing their presence in the emerging business of loans for personal and professional services. There is a striking regional dimension to the developments of the last few years. The emerging banks and the existing ones are competing to expand in South, and North-West India attracted by the growing credit business in a milieu with strong banking habits. This has resulted in a drastic reallocation of total commercial credit from the poorer agricultural states to Delhi, Maharastra and Tamilnadu. The situation is one where private banks are left to "skim the cream" without investing in the longterm development of banking habits.